Effectiveness of Client Specific Planning as an Alternative Sentence, 1981-1982: Washington, DC, and Fairfax, Montgomery, and Prince George Counties - Clements, William H. ([Verlag nicht ermittelbar], 1989)
This data collection was designed to evaluate the Client Specific Planning (CSP) program of the National Center on Institutions and Alternatives (NCIA). The CSP program offers non-incarcerative sentencing options and alternatives prepared for judges and presented by an NCIA caseworker. The study measures the impact of the program on sentence length, sentence severity, the effectiveness of the program at diverting serious felony offenders from incarceration, and the rate, type, seriousness, and timing of recidivism in a 24-month post-sentence risk period. Variables are provided for each defendant on demographic characteristics, criminal history, prior counseling experiences, prior incarceration, charges and dispositions of the recidivist arrests, and types of sentencing alternatives recommended in CSP.